EFFECTIVENESS OF USING THEATER IN TEACHING A FOREIGN LANGUAGE (Scientific journal of the Fergana State University, 2025)
The article is devoted to the study of the effectiveness of using theatricalization in the process of teaching a foreign language. The work analyzes various methods of the theatrical approach and their impact on the development of students' language skills. The article also discusses the psychological and pedagogical aspects of the use of theatrical methods, their impact on student motivation and the creation of a positive emotional climate in the classroom. Based on the results of an experimental study, it is shown that the use of theatricalization significantly increases students’ interest in learning a foreign language, improves their confidence in communication and contributes to a deeper perception of language material.